2007
DOI: 10.1128/aem.01328-06
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin and Shiga Toxin-Encoding Phage Do Not Facilitate Escherichia coli O157:H7 Colonization in Sheep

Abstract: Isogenic strains of Escherichia coli O157:H7, missing either stx 2 or the entire Stx2-encoding phage, were compared with the parent strain for their abilities to colonize sheep. The absence of the phage or of the Shiga toxin did not significantly impact the magnitude or duration of shedding of E. coli O157:H7.The major reservoirs for Shiga toxin-producing Escherichia coli (STEC) are cattle and other ruminants. These bacteria are carried in the gastrointestinal tract and do not cause disease in mature ruminants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Therefore, this study examined the effect of adherence of a wild-type EHEC O157 strain and its vt2-negative mutant on Gb3 expression in IPEC-J2 cells by investigating the expression of Gb3 synthase. Our data show that adherence of the wild-type bacteria resulted in an elevation of the level of expression of (1,2,21,22,25). The reasons for the conflicting results are not known, but they could be due to the different animal species, bacterial strains, and routes of infection.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, this study examined the effect of adherence of a wild-type EHEC O157 strain and its vt2-negative mutant on Gb3 expression in IPEC-J2 cells by investigating the expression of Gb3 synthase. Our data show that adherence of the wild-type bacteria resulted in an elevation of the level of expression of (1,2,21,22,25). The reasons for the conflicting results are not known, but they could be due to the different animal species, bacterial strains, and routes of infection.…”
Section: Discussionmentioning
confidence: 50%
“…For example, introduction of the organism by a route that bypassed most of the gut [31] or the use of animals with no or reduced flora [33] could preclude detection of a role for toxin. Additionally, the conclusions in some of the reports are based on either a single time-point post-infection [29] or a limited temporal analysis [32, 33]. Finally, in one instance the authors excluded a role for Stx in gut adherence yet only measured colonization levels of an Stx-negative E. coli O157:H7 strain without inclusion of a wild-type toxigenic strain for comparison [30].…”
Section: Discussionmentioning
confidence: 99%
“…VT is well established as a major virulence factor of EHEC O157:H7 that plays a central role as a toxin in HUS and HC (39), but its role in adherence is controversial (4). It is only recently that evidence supported a role for VT in adherence to HEp-2 cells and in colonization of the intestine of mice; this enhanced colonization correlated with a VT-induced increase in nucleolin, a receptor for intimin on the host epithelial cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Severe damage due to infection with EHEC is attributable to the cytotoxic verotoxin (VT), which damages epithelial and endothelial cells, leading to bloody diarrhea and HUS (16). Several investigators have reported that VT does not play a role in colonization of the intestine (2,4,34). However, Robinson et al (30) reported recently that VT enhances adherence to epithelial cells and colonization of the mouse intestine by E. coli O157:H7.…”
mentioning
confidence: 99%